Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.4103/0259-1162.179312
|View full text |Cite
|
Sign up to set email alerts
|

Measuring skin to subarachnoid space depth in Egyptian population: A prospective cohort study

Abstract: Background:Lumbar puncture is a difficult medical skill and is used for administering subarachnoid anesthetic medications. Estimation of skin to subarachnoid space depth (SSD) helps to reduce post spinal anesthetic complications.Aims:To measure the SDD in overall Egyptian population and to find a formula for predicting SSD in Egyptian patients.Settings and Design:Four hundred patients of American Society of Anesthesiologist class I and II adult Egyptian patients undergoing surgery using spinal anesthesia in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Taman HI et al 21 in Egyptian population, Prakash S et al 22 and Hazarika R et al 23 in Indian population studied the correlation of skin subarachnoid distance with age, sex, weight and BMI of the patients. They observed that there is positive correlation with skin subarachnoid distance with sex and BMI of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Taman HI et al 21 in Egyptian population, Prakash S et al 22 and Hazarika R et al 23 in Indian population studied the correlation of skin subarachnoid distance with age, sex, weight and BMI of the patients. They observed that there is positive correlation with skin subarachnoid distance with sex and BMI of the patients.…”
Section: Discussionmentioning
confidence: 99%